2022
DOI: 10.11124/jbies-21-00199
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of people with progressive memory disorders participating in non-pharmacological interventions: a qualitative systematic review

Abstract: This review identified, critically appraised, and synthesized the available evidence on the experiences of people with progressive memory disorders who are involved in non-pharmacological interventions.Introduction: Non-pharmacological interventions are widely used to improve the quality of life and general wellbeing of people with progressive memory disorders. While an array of intervention effects has been studied, a systematic review of experiences is needed. First-hand knowledge and experience provides ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 120 publications
(177 reference statements)
0
0
0
Order By: Relevance
“…A preliminary search for existing systematic reviews on this topic was conducted on PROSPERO, JBI Evidence Synthesis, the Cochrane Database of Systematic Reviews and PubMed. Two similar qualitative systematic reviews were identified: those of Gibbor et al [20] and Tuomikoski et al [21]. The scope of Tuomikoski et al's review, which examined the experiences of people with progressive memory disorders who have participated in non-pharmacological interventions, was broader than the proposed review since it evaluated cognitive stimulation alongside other non-pharmacological interventions, such as exercise programs and music therapy [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary search for existing systematic reviews on this topic was conducted on PROSPERO, JBI Evidence Synthesis, the Cochrane Database of Systematic Reviews and PubMed. Two similar qualitative systematic reviews were identified: those of Gibbor et al [20] and Tuomikoski et al [21]. The scope of Tuomikoski et al's review, which examined the experiences of people with progressive memory disorders who have participated in non-pharmacological interventions, was broader than the proposed review since it evaluated cognitive stimulation alongside other non-pharmacological interventions, such as exercise programs and music therapy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Two similar qualitative systematic reviews were identified: those of Gibbor et al [20] and Tuomikoski et al [21]. The scope of Tuomikoski et al's review, which examined the experiences of people with progressive memory disorders who have participated in non-pharmacological interventions, was broader than the proposed review since it evaluated cognitive stimulation alongside other non-pharmacological interventions, such as exercise programs and music therapy [21]. Gibbor et al, on the other hand, focused their review on a specific type of cognitive stimulation intervention: CST and its variations, excluding other forms of cognitive stimulation interventions [20].…”
Section: Introductionmentioning
confidence: 99%